Решить ! 1) 5(x-3)=-2(x-4)+6 2)9/10x=-5 3)-3/7x=-27/49

лпк18 лпк18    2   30.08.2019 15:40    1

Ответы
creatorX creatorX  09.09.2020 14:51
5(х-3) = -2(х-4)+6
5х - 15 =  - 2х + 8 + 6
5х  + 2 х = 14  + 15
7х = 29
х = 29/7
х = 4   1/7

5 ( 4  1/7   - 3) =  - 2 (4  1/7   - 4)  + 6
5  *   1  1/7   =   - 2  *   1/7   + 6
(5*8)/7 =   -   2/7   + 6
40/7  =  5   5/7
5   5/7  =  5   5/7

9/10  * х =  - 5
х =  - 5  :   9/10 =   - 5/1    * 10/9
х = - 50/9
х =  -  5   5/9

9/10   * (-50/9) =  - 5
-50/10  = -5
-5=-5

-3/7   * х = -27/49
х = - 27/49   :   (-3/7) =  - 27/49   *  (-7/3) = (9 * 1) /(7*1)
х = 9/7

- 3/7   *   9/7   =  - 27/49
-  27/49  = - 27/49
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика